Prevalence and clinical correlates of cognitive impairment in adults with plasma cell disorders. Issue 7 (September 2022) - Nakamura, Zev M.; Vohra, Sanah N.; Jensen, Christopher E.; Nyrop, Kirsten A.; Deal, Allison M.; Heiling, Hillary M.; Mangieri, Nicholas J.; Grant, Shakira J.; Lichtman, Eben I.; Rubinstein, Samuel M.; Wood, William A.; Muss, Hyman B.; et al.
Abstract: Introduction: Older adults with plasma cell disorders (PCDs) experience cognitive dysfunction that may be attributable to the disease and associated therapies. Yet, this has seldom been reported in the literature. Our objectives were to describe cognitive function (objective and patient-reported) in adults with PCDs and to explore clinical correlates of cognitive impairment. Materials and Methods: Participants completed a geriatric assessment between March 2018 and February 2020. Cognitive function was evaluated using two objective measures – Montreal Cognitive Assessment (MoCA, cutpoint <26) and Blessed Orientation Memory Concentration Test (BOMC, cutpoint >4) – and two patient-reported outcome (PRO) measures – Patient-Reported Outcomes Measurement Information System Cognitive Function (PROMIS-CF, cutpoint <45) and European Organization for Research and Treatment of Cancer Cognitive Functioning subscale (EORTC-CF, cutpoint <75). Spearman correlations examined relationships among these measures and log binomial regression was used to examine characteristics associated with cognitive impairment, as defined by the MoCA and PROMIS-CF measures. Results: Among 86 participants with a mean age of 69 (range: 46–91), the prevalence of cognitive dysfunction was between 20% (BOMC) and 63% (MoCA). There was moderate correlation among objective measures ( r = 0.51, p < 0.0001), moderate to high correlation among PRO measures ( r = 0.69, p < 0.0001), but no correlation between objective and PRO measures. Factors associated with objective impairment included ≤ high school education (RR 1.46, p = 0.009), living alone (RR 1.42, p = 0.02), relapsed/refractory disease (RR 1.39, p = 0.04), empirically de-intensified induction therapy (RR 1.62, p = 0.008), frailty (RR 1.49, p = 0.04), and peripheral vascular disease (RR 1.54, p = 0.002). Factors associated with PRO impairment included social isolation (RR 3.43, p = 0.003), depression (RR 3.30, p = 0.004) and anxiety (RR 4.43, p = 0.0002), frailty (RR 3.60, p = 0.02), falls in the previous 6 months (RR 2.53, p = 0.02), and deficits in physical function (RR 4.44, p = 0.01). Older age was not associated with either objective or PRO impairment. Discussion: Cognitive impairment, using objective and PRO screening measures, was relatively common in adults with PCDs. Cancer-related factors and medical comorbidities were associated with objective cognitive impairment whereas psychosocial and functional factors were associated with PRO impairment.